2016
DOI: 10.1128/aem.00781-16
|View full text |Cite
|
Sign up to set email alerts
|

Photobacterium damselae subsp. damselae, an Emerging Fish Pathogen in the Black Sea: Evidence of a Multiclonal Origin

Abstract: Photobacterium damselae subsp. damselae is considered to be an emerging pathogen of marine fish of importance in aquaculture, with a notable increase in its geographical distribution during the last several years. In this study, we carried out for the first time to our knowledge a genetic and pathobiological characterization of 14 strains isolated from sea bass (Dicentrarchus labrax) reared in the Southeastern Black Sea, where high mortalities were observed at two aquaculture farms during the summer and autumn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 32 publications
3
56
1
Order By: Relevance
“…1). Although previous studies reported that plasmidless strains show virulence for a variety of fish species (7,17), our study constitutes evidence that hlyA ch (the gene that encodes PhlyC) is a major contributor to virulence of plasmidless strains.…”
Section: Figcontrasting
confidence: 52%
See 4 more Smart Citations
“…1). Although previous studies reported that plasmidless strains show virulence for a variety of fish species (7,17), our study constitutes evidence that hlyA ch (the gene that encodes PhlyC) is a major contributor to virulence of plasmidless strains.…”
Section: Figcontrasting
confidence: 52%
“…P. damselae subsp. damselae is being isolated as a causative agent of disease in novel species of cultivated fish, as well as in fish from areas where it had not been previously reported, such as Egypt (19), Tunisia (20), and the Black Sea (7). The majority of P. damselae subsp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations